2000
DOI: 10.1109/9.847122
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of a queueing system with heterogeneous servers and setup costs

Abstract: This paper considers a queueing model with batch Poisson input and two heterogeneous servers, where the service times are exponentially distributed. The faster server is always on, but the slower server is only used when the queue length exceeds a certain level. Activating the slower server involves fixed set-up costs. Also there are linear operating costs and linear holding costs. The class of two-level hysteretic control rules is considered. Rather than proving the overall average cost optimality of a hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 5 publications
0
10
0
2
Order By: Relevance
“…The problem of an optimal allocation of jobs between heterogeneous servers aiming to minimize the mean number of jobs in the ordinary queueing system was considered in Efrosinin (2004), Lin and Kumar (1984), Luh and Viniotis (1990), Nobel and Tijms (2000), Rosberg and Makowski (1990), Rykov (2001), Rykov and Efrosinin (2002). It was shown that the optimal policy belongs to a class of structured policies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of an optimal allocation of jobs between heterogeneous servers aiming to minimize the mean number of jobs in the ordinary queueing system was considered in Efrosinin (2004), Lin and Kumar (1984), Luh and Viniotis (1990), Nobel and Tijms (2000), Rosberg and Makowski (1990), Rykov (2001), Rykov and Efrosinin (2002). It was shown that the optimal policy belongs to a class of structured policies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some progress has been made in [20], where a model with set-up costs and hysteresis control policy was studied. The paper [23] generalizes results to the case of a multi-server system with a cost structure.…”
Section: Introductionmentioning
confidence: 99%
“…the server with larger mean usage cost has to be used if the queue length reaches some prespecified threshold level. The equivalent system with switching cost was analyzed in [5], where the hysteretic allocation policy took place. Due to this policy the usage of the server with higher mean usage cost is performed via the switch-on and switch-off threshold levels.…”
Section: Introductionmentioning
confidence: 99%